A framework for sustainability analysis in water resources management and application to the Syr Darya Basin - Cai, Ximing; McKinney, Daene C.; Lasdon, L. S. (American Geophysical Union, 2002)
Sustainable water management in irrigation‐dominated river basins attempts to ensure a long‐term, stable, and flexible water supply to meet crop water demands, as well as growing municipal and industrial water demands, while mitigating negative environmental consequences. To achieve this delicate balance, new models are needed which can use indicators of sustainability to guide the decision‐making process. This paper presents a new long‐term modeling framework which uses quantified sustainability criteria in a long‐term optimization model of a basin, ensuring risk minimization in water supply, environmental conservation, equity in water allocation, and economic efficiency in water infrastructure development. “Current” and “future” water supply and demand are combined into a coherent system which takes account of the cumulative effects of short‐term water use decisions and deals with the tradeoffs between the benefits of current and future generations. The modeling framework is demonstrated with an application to the Syr Darya River Basin of central Asia. Model results show the effectiveness of this tool for policy analysis in the context of the river basin.